The THE EFFECT OF SERVICE QUALITY, PRICE, AND PROMOTION ON THE XL PREPAID CARD USER SATISFACTION IN SURAKARTA - Desi Anggrahini (Jurnal Ilmiah Econosains, 2019)
This study aims to determine the effect of service quality, price, promotion of XL prepaid card user satisfaction based on the achieved status. The population in this study is the users of the XL prepaid card in Surakarta in 2017 amounted to 14.536 people. Samples using Slovin amounted to 100 respondents with an accidental sampling technique. This study used explanative research. The results of the data analysis found that the quality of service, price, promotion significantly affect the satisfaction of XL prepaid card users simultaneously or partially while the achieved status variable does not affect the satisfaction of XL prepaid card users. The result of the coefficient of determination (R2) is 88.4%.